2022
DOI: 10.3390/ijerph20010524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality Exercises versus Isokinetic Exercises in comparison with Conventional Exercises on the Imaging Findings and Inflammatory Biomarker Changes in Soccer Players with Non-Specific Low Back Pain: A Randomized Controlled Trial

Abstract: Chronic non-specific low back pain (CNLBP) is the most common musculoskeletal problem. The purpose of this study was to investigate the effects of advanced physiotherapeutic exercise programs on imaging findings and inflammatory biomarkers in soccer players with CNLBP. In total, 60 CNLBP participants were divided into virtual reality exercise (VRE; n = 20), isokinetic exercise (IKE; n = 20), and conventional exercise (n = 20) groups. Pain intensity, imaging findings (muscle cross-sectional area (CSA) and muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The duration of a single VR session ranged from 2 to 40 minutes, and the frequency of treatment ranged from 5 to 7 times a week; all the included studies ranged in duration from a single exercise session to 8 weeks. For the control groups, 5 (31%) studies performed conventional balance function training [ 33 , 34 , 38 - 40 ], 5 (31%) performed conventional physical therapy [ 36 , 37 , 41 , 46 , 47 ], 2 (13%) performed core training [ 43 , 44 ], and the remaining conducted treatments, including sham VR [ 32 ], conventional multimodal pain therapy [ 42 ], waiting lists [ 45 ], and standard care [ 35 ]. The intervention details are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of a single VR session ranged from 2 to 40 minutes, and the frequency of treatment ranged from 5 to 7 times a week; all the included studies ranged in duration from a single exercise session to 8 weeks. For the control groups, 5 (31%) studies performed conventional balance function training [ 33 , 34 , 38 - 40 ], 5 (31%) performed conventional physical therapy [ 36 , 37 , 41 , 46 , 47 ], 2 (13%) performed core training [ 43 , 44 ], and the remaining conducted treatments, including sham VR [ 32 ], conventional multimodal pain therapy [ 42 ], waiting lists [ 45 ], and standard care [ 35 ]. The intervention details are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with CSP develop a systemic inflammatory response and have elevated levels of inflammatory markers in the blood [ 51 ]. Two studies (62 patients) focused on the levels of inflammatory markers (eg, CRP, TNF-α, IL-2, IL-4, and IL-6) by collecting 10 mL of venous blood [ 38 , 39 ]. The results showed that VR therapy significantly improved the level of CRP (WMD=–0.89, 95% CI –1.07 to –0.70, P <.001, I 2 =0%), TNF-α (WMD=–6.60, 95% CI –8.56 to –4.64, P <.001, I 2 =98%), and IL-6 (WMD=–2.76, 95% CI 2.98 to –2.53, P <.001, I 2 =0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with an odd number were therefore assigned to the standard group in the order in which they arrived, while subjects with an even number were assigned to the isokinetic group in the order in which they arrived. In estimating the appropriate sample size for the study, we were guided by the sample size of similar studies, which was 20 subjects per group (22,23) (see the study limitation of our research).…”
Section: Methodsmentioning
confidence: 99%
“…Nambi et al [40] investigated the effects of physiotherapeutic exercise programs on imaging findings and inflammatory biomarkers in soccer players with chronic nonspecific LBP. A total of 60 participants were divided into virtual reality exercise, isokinetic, and conventional exercise groups.…”
Section: Low Back Painmentioning
confidence: 99%